BEHAVIORAL ASPECTS OF HARMONIOUS DEVELOPMENT OF THE TAX SYSTEM OF UKRAINE - Barabash, Lesia (Social Economics, 2021)
In the light of the COVID-19 pandemic, more and more attention of Ukrainian scientists is drawn to non-traditional factors stimulating the development and harmonization of the tax system, which should include behavioral aspects. The purpose of the article was to outline the latter in the conditions of functioning of the tax system of Ukraine. The influence of behavioral factors was assessed based on the expected results of their activation.It is noted that ignoring the above factors encourages taxpayers to make irrational decisions and violations of tax legislation, which is expressed in tax evasion or avoidance. However, the same aspects can be potentially effective in harmonizing the current tax system.To outline the current behavioral aspects of the impact on taxation in Ukraine, the existing results of the tax system were studied, the basic factors influencing them were identified and the desired qualitative effects in the future were outlined.I claim that сurrently, the tax system of Ukraine is characterized by the predominance in the structure of revenues of the Consolidated Budget of Ukraine of the share of indirect taxes over direct ones. And although at the end of 2020 this figure, compared to 1992, decreased by 3.4%, the inflated tax burden is felt by all taxpayers. In addition, excessive fiscalization of the economy does not promote investment activities that could improve the country's economic climate.Outlining the range of main factors that can be used to adjust the economic behavior of taxpayers, as well as factors that directly affect the taxpayer's decision, made it possible to form a list of active behavioral aspects relevant in modern conditions for harmonization of Ukraine's tax system. Among them, there is the transfer of part of the financial obligations to perform direct functions of the state to the payers themselves, in particular by directing funds from the excise tax on fuel for road repairs and rehabilitation, strengthening equity trends by increasing taxation of capital and luxury goods, setting progressive rates taxes, granting benefits and preferences to certain categories of payers; adjusting the preferences of taxpayers through the level of taxation.Under general condition that the state modifies  the tax targets from fiscal to incentive, the result should be a new model of taxpayers' behavior.